NIAT PERILAKU PETANI SAWIT SWADAYA DALAM PENINGKATAN USAHA BERKELANJUTAN DI KABUPATEN SAMBAS PROVINSI KALIMANTAN BARAT - Vicki, Vicki; Nurliza, Nurliza; Dolorosa, Eva (Universitas Sebelas Maret, 2021)
The development of sustainable oil palm plantations as presented in the ISPO (Indonesian Sustainable Palm Oil) framework is important to be implemented. This study aims to analyze the behavioral intentions of independent smallholders in Sambas Regency related to increasing sustainable palm oil business. This study implemented descriptive and inferential analysis by using structural equation modeling (SEM). The results showed that farmers' behavioral intentions are determined by attitudes (general attitudes, personal attitudes, emotional values, and intelligence) and perceptions of behavioral control (experience, knowledge, media, and intervention), which further influence behavior, but subjective norms (age, sex, education, income, and religion) are known not to affect the intention of farmers to behave. In the context of fostering and developing oil palm, farmers began to be fostered to try to work in groups through farmer groups and form cooperatives because ISPO certification will only be given to farmers through farmer groups or cooperatives.